2015
DOI: 10.1186/s12864-015-2026-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis identifies two large deletions in the genome of highly-passaged attenuated Streptococcus agalactiae strain YM001 compared to the parental pathogenic strain HN016

Abstract: BackgroundStreptococcus agalactiae (S. agalactiae), also known as group B Streptococcus (GBS), is an important pathogen for neonatal pneumonia, meningitis, bovine mastitis, and fish meningoencephalitis. The global outbreaks of Streptococcus disease in tilapia cause huge economic losses and threaten human food hygiene safety as well. To investigate the mechanism of S. agalactiae pathogenesis in tilapia and develop attenuated S. agalactiae vaccine, this study sequenced and comparatively analyzed the whole genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The closest GBS fish pathogens with published genomes, GD201008–001 ( 19 ) and HN016 ( 20 ), are serotype Ia ST7 strains that are distant (>4,000 SNPs) from all ST283 strains that our group and others have identified ( 12 ). …”
Section: Discussionmentioning
confidence: 92%
“…The closest GBS fish pathogens with published genomes, GD201008–001 ( 19 ) and HN016 ( 20 ), are serotype Ia ST7 strains that are distant (>4,000 SNPs) from all ST283 strains that our group and others have identified ( 12 ). …”
Section: Discussionmentioning
confidence: 92%
“…Homologous clusters from OrthoMCL were compiled to identify shared and unique genes [ 36 ]. The core genes, new genes, and pan-genome size were calculated for each combination and then extrapolated using several functions to find a best fit from the mean number at each sampling point [ 36 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [11] showed that serial passaging of pathogenic strains of S. agalactiae led to deletions of virulence factors culminating in the production of avirulent strains that were highly protective when used as a live vaccine in tilapia. Similarly, Li et al [8] showed that a serially passaged pathogenic strain of S. agalactiae lost its virulence and when injected as a live vaccine at 10 9 CFU/fish and orally administered at 10 10 CFU/fish showed high protection without causing clinical disease in vaccinated fish.…”
Section: Antigen Delivery Systemmentioning
confidence: 99%